THE EFFICACY OF RECOMBINANT ACTIVATED FACTOR VII (COAGIL VII) FOR TREATMENT HAEMORRHAGE AND HAEMOSTASIS DISORDES DURING THORACIC AORTA OPERATIONS - N. A. TREKOVA; D. A. GUSKOV; A. V. GONCHAROVA; B. A. AKSELROD (Вестник анестезиологии и реаниматологии, 2019)
Goal: to evaluate the efficacy and safety of domestic (home-produced) recombinant factor VIIa (Coagil VII) for massive bleeding and haemostasis disordes treatment in thoracic aorta surgery. Methods. 82 patients undergoing surgery on thoracic aorta with cardiopulmonary bypass and circulatory arrest s were divided in 3 groups. The 1 group included 27 patients with uncomplicated operations, moderate hemorrhage and standart protocol hemostasis management after cardiopulmonary bypass. In 2 group of 26 patients with massive hemorrhage the thrombocytes were used for treatment. In 3 main group (29 patients) with continious bleeding Coagil VII was used additionally. Results. Coagil-VII induction in dose 37–100 mcg/kg was accompanied by prominent decreasing of wound bleeding in 20–25 min, that it allowed to perform sternoraphia. The volume of transfused erythrocytes , fresh frozen plasma and postoperative blood loss were less in comparison with control group and patients where the platelets were used. There were no any complications after Coagil VII induction. Analysis of the hemostasis indices showed decrease of APTT by 13%, PTT by 17% and MNO by 36% after Coagil VII induction. Conclusion. The domestic recombinant factor VIIa (Coagil VII) in dose 66 ± 19,5 mcg/kg is an effective and safe medicine for bleeding and hаemostasis desordes treatment in the patients undergoing aortic surgery